PERAN PEMBIAYAAN PRODUK AR‐RUM BAGI UMKM PADA PT. PEGADAIAN (Persero) CABANG SYARIAH SIMPANG PATAL PALEMBANG - Muftifiandi Muftifiandi (I-Finance Journal, 2015)
The aim of this research is to elaborate the role of ar‐rum productfinancing on small and mideum‐sized enterprises at PT. Pegadaian (Persero) ofSyariah branch Simpang Patal Palembang. Using qualitative approach withopen‐ended interviews, this research finds out that the ar‐rum productfinancing has a distinctive role on small and medium business‐sizedenterprises. After using this kind of financing most of the small and mediumsizedenterprises could increased their capital in order to ensure thesustainability of day to day their business activitiesKey Words: Ar‐Rum Product Financing, Small and Mideum‐Sized Enterprise